Multiculturalism in the Novel of Si Anak Pintar by Tere Liye - Taqwim, Ahsanu; Liliani, Else (PT FORMOSA CENDEKIA GLOBAL, 2024)
Multiculturalism is a form of appreciation and respect for other people regardles of ethnicity, tribe and culture. This research describes the element of multiculturalism in the novel of Si Anak Pintar by Tere Liye. This research uses an interpretative descriptive method by presenting interpretations in descriptive form. The data analysis technique uses reading and note-taking techniques, with four steps, namely: (1) data classification, (2) interpreting the data, (3) interpreting the findings, and (4) writing a report based on the findings. The research results show that the novel of Si Anak Pintar by Tere Liye contains elements of multiculturalism, namely: a sense of solidarity and brotherhood, gender equality, open trade, family values, respect for morals, feeling content in life, and sharing social control.